Simple method for constructing and repairing tissue microarrays using simple equipment. Issue 3 (March 2021) - Zhang, Wei; Qiu, Fuman; Jiang, Qingping; Liu, Shaoyan; Xiong, Zhongtang
Objective: Many methods for tissue microarray (TMA) construction were described in previous reports. Because TMA-based methods are expensive and complicated, their widespread application may be restricted. This study aimed to develop a simple method for TMA construction. Methods: High-density TMAs were constructed using simple equipment, and hematoxylin and eosin and immunohistochemical staining were performed to analyze the effect on the TMA block. Results: A recipient block with 162 holes of 0.9 mm in diameter was prepared using a mini-drill and plastic mold. Tissue cores of 1.0 mm in diameter were obtained from multiple donor blocks with stainless-steel capillary tubes driven by the mini-drill. Under the fixation and guidance of the plastic mold, tissue cores could be easily injected into the holes in the recipient block by inserting a stainless-steel wire into the stainless-steel tube with the tissue core and then pressing using the stainless-steel wire. Conclusion: A high-density TMA block with 162 1.0-mm cores was created. This new modified technique could be a good alternative in many laboratories.